Astragalus trifoliastrum (Fabaceae), a revived species for the flora of Turkey. (7th May 2015) - Bagheri, Ali; Erkul, Seher Karaman; Maassoumi, Ali Asghar; Rahiminejad, Mohammad Reza; Blattner, Frank R.
<x xml:space="preserve">Abstract</x> As the result of surveying the relevant type specimens, together with macro‐ and micro‐morphological studies, chromosome counting and ITS sequencing, Astragalus trifoliastrum was found to be a species independent of A. laguriformis (with which it has peviously been synonymized). In contrast, A. wanensis, assumed to be a synonym of A. trifoliastrum, indeed appears to be identical with A. trifoliastrum. The diploid chromosome number of 2n = 16 is reported for the first time for A. trifoliastrum.